O personagem e os textos : uma análise da atuação do Visconde do Uruguai sobre a abertura do rio Amazonas à navegação internacional - Mattioni, José Victor Dornelles (2018)
This research’s objective is to analyze the actions of Paulino José Soares de Sousa, known by the title of Viscount of Uruguay, for the opening of the international navigation in the Amazon river from the 1850s. In order to do so, we investigate his participation through primary documents such as the Act of 1854, of which he was the rapporteur, and the Opinion of 1865. Thus, we identified how Paulino acquired information about the Amazon region and used official and unofficial Brazilian and foreign sources to elaborate suggestions to the central government of Brazil in the quest to maintain the sovereignty of the Brazilian Empire in the Amazon.